DYNAMIC RELATION OF MONEY VELOCITY, MONEY VOLATILITY AND INFLATION THRESHOLD - Antoni Antoni (Universitas Islam Indonesia, 2011)
This paper investigates relationship between velocity of money, inflation, volatility of money, threshold inflation, output gap, and money velocity gap for two Asean countries, Indonesia and Thailand from 1995:Q1-2010:Q4. The models adopted are Autoregressive Conditional Heteroscedasticity, Hodrick-Prescott and Autoregressive Distributed Lag models. The result shows that relationship between inflation and volatility of money with velocity of money exists in Indonesia, but it does not in Thailand. Threshold inflation does not exist in Indonesia. Meanwhile, it is found that output gap can influence inflation. In addition, the fourth model shows that money velocity gap is not related with inflation for Indonesia only. Keywords: Velocity of Money, Volatility of Money, Inflation Threshold, Output GapJEL classification numbers: E31, E51